The Association between Periodontal Disease and Malnutrition in A Group of Elderly People in Thailand - Rattanasuwan, Kanyawat; Chatkittikunwong, Kunsenee (Khon Kaen University Dental Journal, 2023)
The aim of this study was to determine the association between periodontal disease and malnutrition status in older adults. The factor(s) which are related to malnutrition in older adults with periodontal disease were investigated. Participants > 60 years old with functional and cognitive independent were included in this cross-sectional study. Sociodemographic data, anthropometric measurements, self-rated chewing, periodontal status, number of teeth and functional tooth units (FTUs) were recorded. The Mini Nutritional Assessment (MNA) was used for nutritional status assessment. Eighty-two participants were included in the study. Two groups including normal nutrition group (82.9%) and at risk of malnutrition group (17.1%) were found. A significant association between periodontal disease and risk of malnutrition was not found from this study (p=0.557). A significant difference in nutritional status was found according to education levels (p=0.009). The percentage of participants with insomnia and osteoarthritis was significantly higher in the at risk of malnutrition group than in the other group (p=0.003 and 0.042). It was noticeable that more participants with depression were found in the at risk of malnutrition group than in the other group (14.3% vs 1.5%). Then an association between periodontitis and malnutrition in older adults was not found in this study. The current study suggests an association between insomnia, osteoarthritis and depression with risk of malnutrition. Thus, older adults with these symptoms may be at risk of malnutrition and further study is needed to answer these questions.